2020
DOI: 10.1371/journal.pone.0238419
|View full text |Cite
|
Sign up to set email alerts
|

Grouping crossbred Holstein x Gyr heifers according to different feed efficiency indexes and its effects on energy and nitrogen partitioning, blood metabolic variables and gas exchanges

Abstract: The objectives of this study were: i) to classify animals into groups of high and low feed efficiency (FE) using three FE indexes (Residual feed intake (RFI), Residual weight gain (RG) and Feed conversion efficiency (FCE)), and ii) to evaluate whether crossbreed Holstein x Gyr heifers divergent for FE indexes exhibit differences in nutrient intake and digestibility, energy partitioning, heat production, methane emissions, nitrogen partitioning and blood parameters. Thirty-five heifers were housed in a tie-stal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 43 publications
(102 reference statements)
1
6
0
Order By: Relevance
“…No differences were observed in glucose, insulin, and IGF-1 concentrations, and the glucose:insulin ratio between HE and LE groups for RFI (Table 3), was corroborated in research that found no difference in glucose concentration between HE-RFI and LE-RFI [29]. However, a moderate correlation was observed between glucose and DMI (0.33; p = 0.0017) and between glucose and ADG (0.35; p = 0.0009) (Table 4).…”
Section: Blood Metabolites and Hormonessupporting
confidence: 54%
“…No differences were observed in glucose, insulin, and IGF-1 concentrations, and the glucose:insulin ratio between HE and LE groups for RFI (Table 3), was corroborated in research that found no difference in glucose concentration between HE-RFI and LE-RFI [29]. However, a moderate correlation was observed between glucose and DMI (0.33; p = 0.0017) and between glucose and ADG (0.35; p = 0.0009) (Table 4).…”
Section: Blood Metabolites and Hormonessupporting
confidence: 54%
“…However, milk N secretion is easier to measure than N accretion in growing animals. In growing cattle, most studies have failed to prove this link through N balance measurements 24 , 25 . However, results from our team using a novel isotopic approach applied to this same experimental setup (n = 48) suggested that more efficient animals in terms of RFI also show higher N use efficiency compared to less efficient RFI animals 26 .…”
Section: Discussionmentioning
confidence: 99%
“…The lack of correlation between rumen fermentation parameters and RFI in the pre-weaning phase is probably related to insufficient rumen function in milk-fed animals, as neonatal calves have an underdeveloped rumen until close to weaning [ 16 ], and differences in rumen fermentation products have been reported for RFI-divergent animals in later life [ 39 , 40 ]. In fact, β-hydroxybutyrate levels have been pointed out as a potential marker for the identification of high-efficiency heifers post-weaning [ 40 ]. It is possible that gene expression in rumen epithelium [ 41 ] and epithelium-associated bacteria [ 42 ], rather than fermentation, might be involved in improved efficiency in pre-weaning calves, as it has been indicated for older cattle.…”
Section: Relationship Between Rfi and Nutrient Metabolism In Pre-wean...mentioning
confidence: 99%